Nutritional Habits and Precocious Puberty in Girls: A Pilot Study - Nevra Koç; Hülya Yardımcı; Nazlı Nur Arslan; Seyit Ahmet Uçaktürk (Galenos Yayinevi, 2018)
Aim:Precocious puberty (PP) is defined as the appearance of secondary sexual characteristics before the age of nine in boys or eight in girls. Due to changing socio-economic conditions, nutritional habits and environmental factors, the onset of normal puberty is being seen at younger ages these days. The purpose of this study was to evaluate the dietary habits and environmental factors in cases that presented to or were being followed up by the Child Endocrinology Clinic with symptoms of PP.Materials and Methods:The study group included 50 girls aged 2-8 years who presented with symptoms of PP and whose diagnosis was being monitored. A survey noting food consumption was made recording the girls' dietary habits, fast food consumption and frequency, information about their health, physical activity (PA) and environmental factors using a 24-hour-recall technique.Results:The mean age of the girls was 7.1±0.9 years. According to body mass index z-scores, 62.0% of the girls were overweight [(≥+1 standard deviation (SD)], 34.0% were normal (≥+1 SD - <+1 SD) and 4.0% were underweight. There was a statistically significant difference between the girls' levels of activity and their mean ages (p<0.05). The girls' favorite choices of fast food were hamburgers (20.3%), lahmacun (a thin pizza with spicy meat topping) (11.9%), 32% of the girls were using perfumes or skin creams. Plastic culinary utensils were used in 56% of the children's homes. Of those girls who watched more than three hours of television (TV) a day, 71% were overweight.Conclusion:Increased consumption of fast food containing higher amounts of fat, energy and protein in conjunction with decreased PA, exposure to chemicals that impair the endocrine system and exposure to stimulating devices (TV, computer) may be important factors in the development of PP. Further research is needed to evaluate the negative effects of these factors.